Random access quantum information processors using multimode circuit quantum electrodynamics. Issue 1 (December 2017) - Naik, R.; Leung, N.; Chakram, S.; Groszkowski, Peter; Lu, Y.; Earnest, N.; McKay, D.; Koch, Jens; Schuster, D.
Abstract Qubit connectivity is an important property of a quantum processor, with an ideal processor having random access—the ability of arbitrary qubit pairs to interact directly. This a challenge with superconducting circuits, as state-of-the-art architectures rely on only nearest-neighbor coupling. Here, we implement a random access superconducting quantum information processor, demonstrating universal operations on a nine-qubit memory, with a Josephson junction transmon circuit serving as the central processor. The quantum memory uses the eigenmodes of a linear array of coupled superconducting resonators. We selectively stimulate vacuum Rabi oscillations between the transmon and individual eigenmodes through parametric flux modulation of the transmon frequency. Utilizing these oscillations, we perform a universal set of quantum gates on 38 arbitrary pairs of modes and prepare multimode entangled states, all using only two control lines. We thus achieve hardware-efficient random access multi-qubit control in an architecture compatible with long-lived microwave cavity-based quantum memories. Despite their versatility, superconducting qubits such as transmons still have limited coherence times compared to resonators. Here, the authors show how to use a single transmon to implement universal one-qubit and two-qubit operations among nine qubits encoded in superconducting resonators' eigenmodes.